DESIGN AND FABRICATION OF MULTI-PURPOSE MINERAL LEACHING EQUIPMENT - Ajibola, Olawale; Borisade, Sunday; Adebayo, Abdullahi; Owa, Adebayo; Adigun, Oluwole; Oni, Olamide; Akanni, Princess; Oni, Abayomi; Omoyeni, Dada; Fagbohungbe, Ayodeji; Umunakwe, Reginald; Kolawole, Folorunsho (FUDMA JOURNAL OF SCIENCES, 2021)
With much amount of money the nation had invested into the extractive sector of the economy, minerals are still mined and exported out of the country for beneficiation which results into much economic losses in the mining and extractive industries. The need to reduce the huge amount of losses expended on extracting valuable metals from ores by local miners and out springing cottage industries motivates this work. This report covers the design and construction of a laboratory size leaching equipment suitable for dissolution of clean pulverised minerals in acid and alkaline media via agitation and in-situ leaching techniques in single operation system. The dissolved metals are easily recovered from the solution by other techniques. The design and fabrication is based on the fundamentals of stoichiometric calculations and chemical reactions, engineering design drawings using AUTOCAD and INVENTOR softwares, material selection and safe environmental ethics. The equipment is produced from combination of highly corrosion resistant plastic materials, mild steel, stainless steel and other components. For the purposes laboratory studies, the machine can process about 320-350 kg mineral feeds charged manually and in batches for working period of 1 to 8 hours per day. The estimated fabrication cost is about N194,500.00.